Pengaruh Stimulus Lingkungan Fisik Dan Lingkungan Sosial Terhadap Pembelian Impulsif (Studi Pada Hypermart Ambon City Center Passo Kota Ambon) - Sahertian, Ketrin; Sahertian, Olivia Laura (Arthavidya Jurnal Ilmiah Ekonomi, 2014)
Impulsive buying is unplaned consumer buyingbehaviorwhich isinfluenced by some factors, such as physical and socialsurrounding stimulus. This research's purpose is to analyzephysicalandsocial surrondingtowards impulsive buying desicion.The research wasconducted inHypermart Ambon City Center Passo-Ambon City consumers. The sample was 97 respondents, and used purposive sampling method.Data was collected by questionnaire, interviews and documentation. Nextthe data was analyzed using descriptive analysis and multiple regressionwith SPSS 16.The results show thatphysical and social surroundingssimultaneously and significantly impactimpulsive buying. The results fromthe partial test show that both physical surrounding and socialsurroundingsignificantly impactimpulsive buying.Keyword : Physical Surroundings, Social Surroundings, Impulsive Buying